Scientific Conferences: A Tool to Promote a Positive Attitude towards Science in Secondary Education Students - Gollerizo Fernández, Adrián; Clemente Gallardo, María R. (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
In the past ten years several research studies have highlighted the need to develop positive attitudes toward science amongst Secondary Education students. The purpose of this study is to examine students’ attitudes towards science after their participation in a scientific conference for students. The study involved 19 secondary school students from a public secondary school in Madrid (Spain). A questionnaire was used to collect data about students’ motivation towards science learning. The results of the research show that the participation in a scientific meeting promotes positive attitudes towards science amongst students. This paper concludes with some guidelines for the design participatory science-learning environments.